The role of supply chain sustainability in a corporate social responsibility strategy - Kitrish, E. (Економічний вісник Донбасу, 2017)
The paper attempts to generalize modern approaches to the organization of supply chain management in the context of ensuring business sustainability, which implies a balance between economic, environmental and social components of business functioning. The role and place of management efforts to ensure the sustainability of supply chains in the implementation of the strategy of corporate social responsibility is considered. The introduction of a modern supply chain management system into business practice is of great importance for industrial enterprises of countries with developing market economies, in particular for Ukrainian metallurgical companies. The sharpness of this need for them increases significantly in modern conditions, when they are forced to reorient to new markets for raw materials and marketing products, ensure the sustainability of business and thereby strengthen the enterprise's competitiveness and image. У статті зроблена спроба узагальнити сучасні підходи до організації управління ланцюгами постачання в контексті забезпечення стійкості бізнесу, яка має на увазі забезпечення балансу між економічними, екологічними і соціальними компонентами функціонування бізнесу. Розглянуто роль і місце зусиль менеджменту щодо забезпечення стійкості ланцюгів постачання в реалізації стратегії корпоративної соціальної відповідальності. Введення сучасної системи управління ланцюгами постачання в ділову практику мають велике значення для промислових підприємств країн з ринковою економікою, зокрема для металургійних компаній України. Гострота цієї потреби для них значно зростає в сучасних умовах, коли вони змушені переорієнтуватися на нові ринки сировини і збуту продукції, забезпечують стійкість бізнесу і тим самим зміцнюють конкурентоспроможність підприємства і його імідж. В статье сделана попытка обобщить современные подходы к организации управления цепями поставок в контексте обеспечения устойчивости бизнеса, которая подразумевает обеспечение баланса между экономическими, экологическими и социальными компонентами функционирования бизнеса. Рассмотрена роль и место усилий менеджмента по обеспечению устойчивости цепей поставок в реализации стратегии корпоративной социальной ответственности. Введение современной системы управления цепями поставок в деловую практику имеют большое значение для промышленных предприятий стран с развивающейся рыночной экономикой, в частности для металлургических компаний Украины. Острота этой потребности для них значительно возрастает в современных условиях, когда они вынуждены переориентироваться на новые рынки сырья и сбыта продукции, обеспечивают устойчивость бизнеса и тем самым укрепляют конкурентоспособность предприятия и его имидж.